Effect of mindfulness-based stress reduction on somatic symptoms, distress, mindfulness and spiritual wellbeing in women with breast cancer: Results of a randomized controlled trial. (May 2015) - Würtzen, Hanne; Dalton, Susanne Oksbjerg; Christensen, Jane; Andersen, Klaus Kaae; Elsass, Peter; Flyger, Henrik L.; Pedersen, Anne E.; Sumbundu, Antonia; Steding-Jensen, Marianne; Johansen, Christoffer
Abstract Background. Women with breast cancer experience different symptoms related to surgical or adjuvant therapy. Previous findings and theoretical models of mind–body interactions suggest that psychological wellbeing, i.e. levels of distress, influence the subjective evaluation of symptoms, which influences or determines functioning. The eight-week mindfulness-based stress reduction (MBSR) program significantly reduced anxiety and depression in breast cancer patients in a randomized controlled trial (NCT00990977). In this study we tested the effect of MBSR on the burden of breast cancer related somatic symptoms, distress, mindfulness and spiritual wellbeing and evaluated possible effect modification by adjuvant therapy and baseline levels of, distress, mindfulness and spiritual wellbeing. Material and methods. A population-based sample of 336 women Danish women operated for breast cancer stages I–III were randomized to MBSR or usual care and were followed up for somatic symptoms, distress, mindfulness skills and spiritual wellbeing post-intervention and after six and 12 months. Effect was tested by general linear regression models post-intervention, and after six and 12 months follow-up and by mixed effects models for repeated measures of continuous outcomes. Effect size (Cohen's d) was calculated to explore clinical significance of effects among intervention group. Finally, modification of effect of MBSR on burden of somatic symptoms after 12 months' follow-up by adjuvant therapy and baseline levels of, distress, mindfulness and spiritual wellbeing were estimated. Results. General linear regression showed a significant effect of MBSR on the burden of somatic symptoms post-intervention and after 6 months' follow-up. After 12 months' follow-up, no significant effect of MBSR on the burden of somatic symptoms was found in mixed effect models. A statistically significant effect of MBSR on distress was found at all time-points and in the mixed effect models. Significant effects on mindfulness were seen after six and 12 months and no significant effect was observed for spiritual wellbeing. No significant modification of MBSR effect on somatic symptom burden was identified. Conclusion. This first report from a randomized clinical trial on the long-term effect of MBSR finds an effect on somatic symptom burden related to breast cancer after six but not 12 months follow-up providing support for MBSR in this patient group.